Eksistensi Hukum Pencatatan Perkawinan Dalam Reformasi Hukum Keluarga Di Dunia Islam - Afrilian, Andre; Khairul Akmal, Khairul; Rizal, Muhammad Akmalul (Fakultas Syariah IAIN Ponorogo, 2024)
Legal reforms carried out by Islamic countries since the beginning of the 20th century starting with Turkey in 1917, then Egypt (1920 and 1929), Jordan (1951), Syria (1953) and Tunisia in 1956 with the publication of the Code of Personal Status Law or Majallah al-Ahwal ash-Syakhsiyah. Then several countries in Asia such as Indonesia Malaysia and others. The material of family law reform in general is about marriage registration because it did not exist at the time of the prophet or the companions and the classical fiqh books. If reviewed, marriage registration has positive values for the sake of order and convenience in this modern era. This research is a library research that examines legal issues by relying on secondary materials, analyzing and then concluding using the theory of legal modernization. In this paper, the author tries to classify the provisions of marriage registration based on three sides, the law of marriage registration, sanctions and registration mechanisms in various Muslim countries and identify the extent to which some Islamic countries depart from the teachings of classical fiqh in reforming family law. The regulation of marriage registration is different in every Muslim country, some of which strictly enforce it so that it determines it as a crime for violators or only makes registration as an administrative requirement, while in terms of the mechanism it is also applied differently in each country.